1
$\begingroup$

I have the polynomial $P(x) = x^3+mx^2-3x+1, m\in \mathbb{R}$. I need to find $x_1^3+x_2^3+x_3^3$ as a $m$ function.

I tried to use Viette equations: $x_1+x_2+x_3 = m, x_1x_2+x_1x_3+x_2x_3 = 3, x_1x_2x_3 = 1$ Then I expanded $(x_1+x_2+x_3)^3 = (x_1^3+x_2^3+x_3^3) + 3(x_1^2x_2+x_1^2x_3+x_1x_2^2+x_2^2x_3+x_1x_3^2+x_2x_3^2) + 6x_1x_2x_3$. After that I expanded $(x_1x_2+x_1x_3+x_2x_3)^2 = 2(x_1x_2x_3)+x_1^2x_2^2+x_1^2x_3^2+x_2^2x_3^2$. I don't know if my way of doing it is the right way, and if it is can you help from this point on?

$\endgroup$
1
$\begingroup$

We have that $x^3_1+x^3_2+x^3_3$ is symmetric (fixed by any element of $S_3$).

Therefore, you may express $x^3_1+x^3_2+x^3_3$ using only the elementary symmetric polynomials.

You may use symmetric reduction on wolframalpha to deduce that:

$x^3_1+x^3_2+x^3_3=(x_1+x_2+x_3)^3-3(x_1x_2+x_2x_3+x_1x_3)(x_1+x_2+x_3)+3x_1x_2x_3$.

Now plug in to get $x^3_1+x^3_2+x^3_3$ in terms of the coefficients.

I believe you should get $(-m)^3-3(-3)(-m)+3(-1)=-m^3-9m-3$

$\endgroup$
  • $\begingroup$ I used symmetric polynomials, but the result shouldn't be $-m^3-6m^2+9m$? $\endgroup$ – Raducu Mihai Jun 12 '19 at 16:26
  • $\begingroup$ In your original post you have $x_1+x_2+x_3=m $ instead of $-m$, $x_1x_2+x_2x_3+x_1x_3=3$ instead of $-3$ and $x_1x_2x_3=1$ instead of $-1$. Is that why? $\endgroup$ – Locally unskillful Jun 12 '19 at 16:28
  • $\begingroup$ Yeah, I think so. Anyways symmetric polynomials are what I need. Thank you for the help. $\endgroup$ – Raducu Mihai Jun 12 '19 at 16:33
  • $\begingroup$ May I ask you another question about this exercise ?I don't know if it is a good idea to post a new question. $\endgroup$ – Raducu Mihai Jun 12 '19 at 16:38
1
$\begingroup$

Since $x_1,x_2,x_3$ are the roots we find that $x_1^3=3x_1-mx_1^2-1$ similarly for $x_2,x_3$ adding the three equations we find that $x_1^3+x_2^3+x_3^3=3(x_1+x_2+x_3)-m(x_1^2+x_2^2+x_3^2)-3$ we see that $(x_1+x_2+x_3)^2=x_1^2+x_2^2+x_3^2+2(x_1x_2+x_2x_3+x_1x_3)$ thus the required value is $x_1^3+x_2^3+x_3^3=3(-m)-m(((-m)^2)-2(-3))-3=-3m-m^3-6m-3=-m^3-9m-3$

$\endgroup$
  • $\begingroup$ $-m^3-9m-3$ I think. $\endgroup$ – Nosrati Jun 12 '19 at 16:20
  • 1
    $\begingroup$ You should have $x_1+x_2+x_3=-m.$ $\endgroup$ – Thomas Andrews Jun 12 '19 at 16:21
  • $\begingroup$ You should also have $x_1x_2+x_2x_3+x_1x_3=-3.$ You have $3.$ $\endgroup$ – Thomas Andrews Jun 12 '19 at 16:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.